PERTANGGUNGJAWABAN PPAT TERHADAP PEMBUATAN SURAT PERNYATAAN KEABSAHAN DAN KEBENARAN DOKUMEN ELEKTRONIK - Meiyona, Ulfa Roffilah; Shaleh, Ali Ismail (Jurnal Hukum Bisnis Bonum Commune, 2022)
Statement of Validity and Truth Documents issued by PPAT can be said to be valid as an underhand deed and can be used as evidence in court, the statement issued by the Land Deed Making Official must be examined carefully and the Land Deed Making Officer must truly apply the principle of prudence. -be careful. The type of research that will be used in this research is normative legal research, using library materials or secondary data, and this research is descriptive. As a result, about the validity of the statement letter and the truth of this document, it can be said that the statement issued by the PPAT is valid, regulated by legislation in which the existence of a statement of validity and correctness of this document must exist before registration of mortgage rights electronically is carried out by provisions of origin 10 paragraph (4) of the Government Regulation of Agrarian and Spatial Planning or the National Land Agency Number 5 of 2020, which explains that the cover letter on the validity and correctness of documents issued by PPAT is mandatory and becomes the responsibility of PPAT.